Space-time behavior of Klang Valley region slope failures - Thanapackiam, P; Khairulmaini, O.S; Fauza, A. G (Universiti Kebangsaan Malaysia, 2012)
In the last decade slope failure intensity and frequency has increased. This article investigates slope failure distribution and trend change and the tendency of spatial direction of slope failures in the Klang Valley Region (KVR) of Malaysia. The change in land cover especially for urbanization and population pressure has notably influenced spatial and temporal variations in slope failure occurrences in the KVR. This study recognized two significant impacts of slope failures: increase in intensity and frequency of slope failures from 1991 to November 2011 and spatial direction of slope failures in the KVR. Both of these effects create severe stresses on the population of the KVR. The study observed that the temporal and spatial advances of slope failures would continue to increase in intensity and frequency in the not so distant future as the environment would become more stressful as a result of urbanization. The knowledge generated from the work would be valuable to all stakeholders affected by slope failures in the KVR and lead the way towards achieving a more sustainable slope development planning in the future.